PEMODELAN EKONOMETRIK GUNA PENGEMBANGAN DAYA SAING EKSPOR AGROINDUSTRI LEMAK DAN BUBUK KAKAO DI INDONESIA - Jono M. Munandar; Joko Purwono; Nadhry Nadirman (Jurnal Manajemen & Agribisnis, 2006)
As the country continues efforts  to liberate its market, Indonesias cocoa agroindustries now face a tough competition from industries of developed countries. Many of these industries had already felt the impact of their lack of competitiveness, causing them to lose their marketshare. The objective of this research is to analyze and identify the key determinants of cocoa agroidustry export competitiveness and build an econometric model. Furthermore this research also attempts to forecast the export competitiveness of Indonesian cocoa agroindustries. Results of econometric analysis showed that factors such as: exchange rate index, prices of related commodities, technological advances, per-capita income of Indonesia, and per-capita income of importing countries are factors influencing the export competitiveness of cocoa butter. While cocoa powder export competitiveness is influenced by exchange rate, interest rate, degree of trade liberalization, price of related goods, per-capita income of Indonesia, and per-capita income of importing countries. Furthermore it is forecasted that both commodities of the industry would expirience an increase of export competitiveness in the future.